Decentralizacja a efektywność sektora publicznego - Zalewski, Alojzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
It is usually claimed that the decentralization of the public sector contributes to the improvements in efficiency and quality of its services and their responsiveness to social needs. These are expected outcomes rather than real ones. Research findings indicate that decentralization is a necessary, but not sufficient condition for the attainment of its benefits. Improvement in efficiency and quality of public services requires the fulfillment of many additional conditions which eliminate potential threats to decentralization like improper assignment of authority to levels of government, alienation of power, corruption, nepotism, clientelism etc. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 589-595